DOES ILLUMINATION OF NON-MATURE CEREAL KERNELS DURING DRYING AFFECT THE GERMINATION ABILITY? - Małuszyńska, Elżbieta; Stefański, Piotr; Matysik, Przemysław; Nita, Zygmunt; Rybka, Krystyna (Plant Breeding and Seed Science, 2016)
The principle of the market competitiveness of breeding companies implicates a fast production of new varieties. One way to achieve this goal brings single seed descent (SSD) methodology, which requires kernels collection (18-23 days after pollination) , fast drying amd germination. Seed drying conditions influence the germination. In present work the influence of lightings: Sanyo LED and incandescent lamp vs. dark control during drying were studied. Kernels were harvested 18 and 23 days after pollination of wheat, triticale and barley cultivars grown in the same field experiment in 2015. It was found that: • the germination ability of non-mature kernels depends on all studied factors: lighting during drying, terms of harvesting and the interaction light * term; • non mature kernelsare more sensitive to drying conditions; • lighting during seeds drying can have a positive effect on ability to germination; • for breeding practice it would be better to harvest kernels at 23 DAF and dry them at room conditions under incandescent lamp.